Plastic deformation behavior and constitutive modeling of Cu-50Ta alloy during hot compression. (20th January 2022) - Pu, Bo; Song, Ping; Li, Wen-Bin; Yao, Wen-Jin; Wang, Xiao-Ming
Abstract: This paper presents a study on plastic deformation behavior of Cu–50Ta alloy at temperatures of 286–473 K and strain-rate of 0.01–6200 s −1 . The effects of temperature, strain-rate, and strain on the yield strength, flow stress, and strain-rate sensitivity coefficient were determined. A phenomenological model was established to predict variation of the strain-rate sensitivity coefficient for Cu–50Ta alloy under dynamic compression. A Johnson–Cook constitutive model was established to predict the equivalent stress–equivalent plastic strain relationship under extreme deformation (high temperature and strain-rate). The results showed that the plastic deformation behavior of Cu–50Ta alloy was affected by temperature, strain-rate, and strain. The material exhibited obvious strain-rate strengthening and thermal softening. As the strain-rate increased, the yield strength logarithmically increased. At a temperature of 286 K, the strain-rate increased from 0.01 s −1 to 6200 s −1, and the yield strength increased from 543.75 MPa to 881.13 MPa. In addition, the yield strength linearly decreased as the deformation temperature increased. Under conditions of dynamic deformation, the variation of strain-rate sensitivity coefficient could be expressed as a function of strain-rate and strain. The phenomenological model accurately described the variation of the strain-rate sensitivity coefficient of Cu–50Ta under dynamic deformation conditions. The Johnson–Cook constitutive parameters, calibrated by experimental data, described the plastic deformation behavior of the alloy under high-velocity impact.